The Springs [advertisement cover], January 1957 - CONFIRM LOCATION BEFORE UPLOADING (1957)
January 1957 issue of The Springs advertisement publication featuring a drawing of the The Springs Restaurant in the Cameron Center in Palm Springs, California.